Bahasa Inggris: Bahasa Indonesia - Ramadhan Akbar, Hafiz (Journal of Economic and Business Analysis, 2025)
This study aims to analyze the risks in managing zakat funds at the Semingin Makmur Mosque and the implementation of risk management to maintain trust and management effectiveness. The method used is qualitative with a case study through interviews and observations of mosque administrators and the zakat payer. The results show that the main risks include operational, distribution, and reputational risks due to error-prone manual management systems. Risk management is carried out by identification, analysis, and mitigation through increased transparency, accountability, and socialization. The research recommends the development of a more professional and integrated zakat management system to minimize risks and increase public trust.